Optimizing Traffic Community Education to Reduce Traffic Violations by Students in the West Lombok Police Legal Area - Gandha Satria Alfarizi (Advances in Police Science Research Journal, 2021)
This research is motivated by the increase in traffic violations committed by students at the West Lombok Police. In this case, the Police have a responsibility to reduce and prevent these problems. The purpose of this study is to describe the implementation of direct social education to students in West Lombok, to find out the factors that influence its implementation and to optimize the activities of social education to reduce traffic violations by students in West Lombok. This research was conducted with a qualitative approach, using descriptive research methods, data validation by data triangulation and data collection techniques with interviews and document studies. Based on the results of the research, the implementation of community education was not optimal because the ability of members was still lacking and was constrained by the covid 19 pandemic. Factors that influenced the implementation of social education for students were both supportive and hindering factors, namely HR factors, sarpras factors and organizational policy factors. To optimize the implementation of community education directly to students, it is suggested that the ability of the personnel of the dikyasa unit can be improved through vocational education or increasing the competence of personnel so that personnel have good social communication to the community as well as the provision of rewards and punishments and more attention to members in order to increase the work motivation of personnel. Conducting alternative education to schools online because of this pandemic period so that education can still be done to students and prepare interesting and systematically arranged material to make it more interesting and easier to understand so as to prevent traffic violations by students.